Antibiotic Prevention for Maternal Group B Streptococcal Colonization on Neonatal GBS-Related Adverse Outcomes: A Meta-Analysis - Li, Shunming; Huang, Jingya; Chen, Zhiyao; Guo, Dan; Yao, Zhenjiang; Ye, Xiaohua (Frontiers in Microbiology, 2017)
Maternal colonization with group B Streptococcus (GBS) during pregnancy increases the risk of neonatal infection by vertical transmission. However, it remains unclear whether treating all colonized women during labor exposes a large number of their neonates to possible adverse effects without benefit. We performed a meta-analysis to assess the effect of intrapartum antibiotic prophylaxis on neonatal adverse outcomes. We identified studies by searching several English and Chinese electronic databases and reviewing relevant articles. Data were pooled using fixed-effects or random-effects meta-analysis, and for each outcome both risk ratio (RR) and 95% confidence intervals (95% CIs) were calculated. Fourteen studies (2,051 pregnant women and 2,063 neonates) were included, comprising 13 randomized clinical trials and 1 cohort study. Antibiotic prophylaxis is associated with a significant reduced risk of all cause infections (RR = 0.28, 95% CI = 0.18–0.42), GBS infection (RR = 0.24, 95% CI = 0.13–0.44), early-onset GBS infection (RR = 0.24, 95% CI = 0.13–0.45), non-GBS infections (RR = 0.34, 95% CI = 0.20–0.59), and GBS colonization (RR = 0.10, 95% CI = 0.06–0.16). But no significant reduction was observed in late-onset GBS infection, mortality from early-onset GBS infection or from non-GBS infections. Notably, no significant differences were found between ampicillin and penicillin prevention for neonatal adverse outcomes. Our findings suggest that antibiotic prophylaxis is effective in reducing neonatal GBS colonization and infection.